Analysis of collaborative control of dairy product supply chain quality based on evolutionary games: Perspectives from government intervention and market failure - Mingde Yang; Cem Işık; Jiale Yan (Heliyon, 2023)
Dairy quality affects the health and quality of life of consumers. Implementing supply chain management and collaborative quality control is an effective way to solve dairy quality problems. Based on the perspective of the combination of market failure and government intervention, this paper analyzes the conditions for the realization of collaborative quality control between dairy farmers and dairy processors. At the same time, this paper uses relevant data to verify the applicability of the model and the accuracy of the conclusions. The findings show that both low yields and high spillovers lead to market failures. When farmers adopt advanced prevention strategies and dairy processors adopt advanced inspection strategies with low yields, basic prevention and basic inspection will be the best combination of quality control strategies for both parties. In this case, the government should subsidize the advanced control strategy to provide adequate subsidies. This will provide incentives for both parties to work together to ensure the quality of dairy products. Secondly, when farmers adopt advanced prevention strategies or dairy processors adopt advanced inspection strategies yields increase but spillover rates are higher. Advanced prevention, basic inspection or basic prevention, advanced inspection would be the optimal combination of strategies for both parties. At this point, the government should increase the penalties. The simulation results further indicate that the government subsidy is more effective for dairy farmers. Government penalties have both the positive and negative reinforcing effects.